New species of Cerambycidae (Coleoptera) from South and Central America - Galileo, Maria Helena M. (Zookeys, 2015)
Abstract. Three new species are described: Tropidion birai (Cerambycinae, Neoibidionini) from Bolivia; Chrysoprasis birai (Cerambycinae, Heteropsini) from Panama; and Recchia nearnsi (Lamiinae, Aerenicini) from Bolivia. The new species are included in amended versions of previously published keys to species of each genus.